Development of the Intercultural Competence in the Initial Foreign Language Teacher Education - Mardešić, Sandra (Array, 2012)
The contemporary research in initial teacher education is oriented towards development of student - teacher teaching competences through the reflective approach and experiential learning. In 2008 in Croatia, in the context of changes in teacher education at the university level within the 'Bologna reform process', a new competence-development curricula was introduced in initial foreign language teacher education. The development of foreign language teacher competence and its components within the new university curricula were examined through the application of the reflective approach and a new instrument, the European portfolio for foreign language teachers. The participants in this study were 66 student- teachers of English, French, and Italian from three Croatian universities. Research was conducted during the practical part of their education in Croatian schools. A mixed research method was applied. It included a quantitative analysis of students’ self- evaluations of gained competences according to the descriptors in the portfolio and a qualitative analysis of a semi - structured interview with the participants about their experiences in working with a portfolio. The results of this research show that new foreign language teacher education programs do not sufficiently develop certain components of teacher competence such as the intercultural competence. Even though that component is stressed in the ministerial programs for foreign language teaching in public schools and it is formally included in the university curricula, the students seem to fail to recognize the connection between language and culture and are more oriented towards teaching methodology of reading, listening, speaking and writing.